(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The systematic structure of the flora of the ruderal vegetation of Ukraine, which includes 1476 species of vascular plants belonging to 570 genera and 116 families, was analyzed. Ecologically close pioneer vegetation – presented respectively by 844 species from 338 genera and 80 families. The ten leading families (Asteraceae, Poaceae, Fabaceae, Brassi-caceae, Lamiaceae, Rosaceae, Apiaceae, Caryophyllaceae, Scrophularia-ceae and Cyperaceae) in ruderal communities combine 59.5 % of species. The largest number of species is noted for the communities of the class Artemisietea vulgaris – 1055 (48.6 % of the entire flora of ruderal vegeta-tion), the slightly less – for the classes Stellarietea mediae – 718 (48.6 %), Galio-Urticetea – 570 (38.6 %), Robinietea – 460 (31.2 %). The smallest number of species was found in the communities of classes Polygono-Poetea annuae – 291 (19.7 %), Plantaginetea majoris – 286 (19.4 %), Bidentetea – 227 (15.4 %), Epilobietea angustifolii – 193 (13.1 %). Family spectra of coenofloras classes of ruderal vegetation is given. The systematic structure of the synanthropic fraction of the flora of ruderal vegetation is considered. It includes 526 species belonging to 271 genera and 66 families. The largest amount of synanthropic species was found in the coenofloras of Polygono-Poetea annuae – 56 %, Plantaginetea majoris – 51 %, Stellarie-tea mediae – 49 %, Bidentetea – 45 %, less of them in Robinietea – 41 %, Galio-Urticetea – 38%, Artemisietea vulgaris – 38 %, the smallest – Epilobietea angustifolii – 29 %. The spectrum of the ten leading families of the alien fraction of the coenofloras includes 190 species. It consists of Asteraceae (50 species), Brassicaceae (35), Poaceae (28), Fabaceae (16), Apiaceae, Chenopodiaceae (14 in each), Lamiaceae (12), Amaranthaceae, Scrophulariaceae, Malvaceae (7 species each). The largest number of them is noted for coenofloras of the classes Stellarietea mediae and Artemisietea vulgaris.